National Program, Local Response: Dynamic of Unconditional Cash Transfer Distribution to Poor Families in Maros Regency, Indonesia - Jaelan Usman; Muhammad Rusydi; Mahnoor Farooq (Journal of Government and Civil Society, 2022)
This study aims to explore the implementation of social assistance programs in improving the welfare of the poor affected by Covid-19 in Maros Regency. This is based on the consideration that the Family Hope Program is a conditional social assistance program, namely Beneficiary Families in supporting the improvement of the welfare of the poor between generations. We investigated the contribution of various possible pathways to the program’s overall impact, including education, health, consumption, caregiver stress levels and life satisfaction, perceived social support, and participation in hard and unpleasant work. The method used is qualitative-explorative with a phenomenological approach, to explore the Unconditional Cash Transfer (BLT) program to help the poor during the COVID-19 pandemic in Maros Regency, data analysis using Nvivo 12 Pro to interpret phenomena more deeply to get the best findings. The results of this study underline that unconditional cash grants are used on a scale that is getting bigger as part of Indonesia’s national social protection system. Unconditional Cash Transfer (BLT) distributed to poor families in Maros Regency aims to ease the economic burden due to Covid-19 Pandemic. Then the Maros Regency Government integrated social programs in collaboration with the Central Government, Regional Social Institutions, and Ombudsman to help poor families avoid economic, health, and education difficulties during Covid-19 Pandemic in Maros Regency. Penelitian ini bertujuan untuk mengeksplorasikan pelaksanaan program bantuan sosial dalam peningkatan kesejahteraan masyarakat miskin yang terdampak akibat Covid-19 di Kabupaten Maros. Hal ini didasarkan pertimbangan bahwa Program Keluarga Harapan adalah program bantuan social yang bersyarat, yaitu Keluarga Penerima Manfaat dalam mendukung peningkatan kesejahteraan masyarakat miskin antar generasi. Kami menyelidiki kontribusi berbagai kemungkinan jalur untuk dampak program secara keseluruhan, termasuk pendidikan, kesehatan, konsumsi, tingkat stress pengasuh dan kepuasan hidup, dukungan sosial yang dirasakan, dan partisipasi dalam kerja keras dan tidak menyenangkan. Metode yang digunakan kualitatif-eksploratif dengan pendekatan fenomenologi, untuk mengeksplorasikan program bantuan langsung tunai (BLT) untuk membantu masyrakat miskin di masa pandemi covid-19 di Kabupaten Maros, analisis data menggunakan Nvivo 12 Pro untuk menginterpertasikan fenomena lebih mendalam untuk mendapatkan temuan terbaik. Hasil penelitian ini menggarisbawahi bahwa hibah tunai tanpa syarat, yang digunakan dalam skala yang semakin besar sebagai bagian dari sistem perlindungan sosial nasional di Indonesia. Bantun Langsung Tunai (BLT) yang disalurkan untuk keluarga miskin di Kabupaten Maros bertujuan untuk meringankan beban ekonomi akibat pandemi covid-19. Kemudian Pemerintahan Kabupaten Maros melalukan integrasi program sosial yang bekerjasama dengan pemerintah pusat, lembaga social daerah, dan Ombusman untuk membantu keluarga miskin terhindar dari kesulitan ekonomi, Kesehatan dan pendidikan selama pandemi Covid-19 di Kabupaten Maros.